Biotinylated carboxymethyl chitosan/CaCO3 hybrid nanoparticles for targeted drug delivery to overcome tumor drug resistance. Issue 73 (20th July 2016) - Wu, Jin-Long; He, Xiao-Yan; Jiang, Pei-Yuan; Gong, Meng-Qing; Zhuo, Ren-Xi; Cheng, Si-Xue
Abstract : A tumor targeted nano-sized self-assembled drug delivery system could efficiently co-deliver an anti-cancer drug and a drug resistance inhibitor to tumor cells and achieve an improved therapeutic efficiency through inhibition of P-gp function. Abstract : A tumor targeted nano-sized drug delivery system was prepared for co-delivery of an anti-tumor drug and a drug resistance inhibitor to overcome multidrug resistance (MDR) in cancer chemotherapy. The drug carrier, biotinylated carboxymethyl chitosan/CaCO3 (BCMC/CaCO3 ) hybrid nanoparticles with biotin as a target ligand was prepared by self-assembly in an aqueous solution. The hybrid nanoparticles exhibited a spherical shape with a hydrodynamic size less than 200 nm. An anti-cancer drug (doxorubicin hydrochloride, DOX) and a P-glycoprotein inhibitor (tariquidar, TQR) were co-loaded in the hybrid nanoparticles to obtain BCMC/CaCO3 /DOX/TQR nanoparticles. For comparison, CMC/CaCO3 /DOX/TQR nanoparticles without biotin ligands were also prepared. An MTT assay was employed to evaluate the cell inhibition effects of the drug loaded nanoparticles on both non-resistant cells (HeLa) and drug resistant cells (MCF-7/ADR). The in vitro study showed that BCMC/CaCO3 /DOX/TQR nanoparticles exhibited obviously enhanced cell uptake and nuclear localization as compared with the free DOX and the single-drug loaded nanoparticles (BCMC/CaCO3 /DOX and CMC/CaCO3 /DOX) because of the efficient inhibition of P-glycoprotein (P-gp) mediated efflux. Moreover, compared with the nanoparticles without biotin moieties, the nanoparticles with biotin ligands showed stronger cell inhibition and increased cellular uptake in tumor cells. All these results indicated that the biotinylated hybrid nanoparticles have promising applications for co-delivery of multiple drugs to effectively overcome cancer drug resistance.